Rapid Remission in Peripheral T-Cell Lymphoma of the Nasal Type by the Bortezomib plus CHOP Therapy. (19th December 2010) - Xue, Li-Jun; Mao, Xiao-Bei; Liu, Xiao-Bei; Su, Quan-Sheng; Yu, Hong-Ju; Yang, Ji-Hong
Abstract : Peripheral T-cell lymphoma (PTCL) is rare and difficult to treat for its high relapse rate. The authors report a case of PTCL of the skin, regarding which clinical and pathological features, treatment, and prognosis were discussed. A 66-year-old woman was admitted with complaints of enlarging erythematous noduloplaques on the right anterior tibial skin for one year and similar lesions on the left for 6 months. Surgical resection of right leg lesion and biopsy of enlarged inguinal lymph nodes histologically indicated a PTCL of the nasal type. The patient was treated by CHOP plus bortezomib, reached complete remission just after two courses of chemotherapy and then received another two as consolidation. The patient remained in remission for 11 months until local relapse. As for cutaneous lesions, detailed lymph node examination and prompt tissue biopsy are judicious choices prior to any medical management. The chemotherapy consisting of bortezomib and CHOP is safe and efficient in PTCL of the skin.